EUCALYPTUS ‘GG 100’ RESPONSE TO SIMULATED DRIFT OF ORTHOSULFAMURON - do Nascimento Tardeli, Mayara Jade [UNESP]; Bidóia, Vitor Simionato [UNESP]; Cesarin, Anne Elise [UNESP]; da Costa Aguiar Alves, Pedro Luis [UNESP] (My University, 2024)
Plant growth regulators and low doses of herbicides are used in some crops in order to achieve satisfactory yields. These compounds can promote qualitative and/or quantitative morphological or physiological changes in plants, such as the inhibiting and delaying the vegetative development in the early maturation or in sugar accumulation in sugarcane crops. The application of these products through spraying aims to reach the target crop, for example, the sugarcane fields, however, some neighboring crops may be contaminated through drift. The present study aims to evaluate the effects of simulated drift of orthosulfamuron on the initial growth of Eucalyptus urophylla seedlings, clone GG 100. The experiment was installed in pots of 5 L capacity in a completely randomized design, with nine treatments and four replicates. The treatments consisted of the following nine increasing doses of orthosulfamuron ripener: 0; 1.19; 2.39; 4.78; 9.56; 19.12; 38.25; 76.5; and 127.5 g a.i. ha-1. The height of the eucalyptus plants was evaluated at 0, 14, 28, 42, and 63 days after application (DAA). At 63 DAA, in the end of the experiment, the stem diameter, leaf area, and the dry matter of leaves, stems, and roots were evaluated. Results show that there were no deleterious effects of the drift of orthosulfamuron up to the dose of 127.5 g a.i. ha-1 on the development and growth of E.urophylla seedlings, clone GG 100, up to 63 days after application.
Simulação de deriva de orthosulfamuron em eucalipto ‘GG 100’
Keywords: Eucalyptus urophylla; Growth; Ripeners